Usulan Perbaikan Tata Letak Fasilitas pada Sahabat Mart - Rahmawati Liswahyuni Dwi Wardhani; Nisrina Ayushafa Deanova; Suci Hakimah; Andini Firannisa; Jelianus Nduru (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The preparation of the layout is something that needs to be considered in forming a factory or a business. The purpose of this study is to prove, test, and verify the retail layout of Sahabat Mart with the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods and evaluate whether the layout is effective for employees and consumers. The type of research used is primary and secondary data. The layout of Sahabat Mart consists of several parts, namely parking, seating, cashier, display room, warehouse, and toilet. Based on the results of the research, the state of layout placement at Sahabat Mart has a less effective placement, including a less optimal warehouse placement position because it is far from the parking lot, making the process of transporting goods less efficient. So the ARC and TCR methods are used. The results of the ARC calculation with the TCR assessment show the largest value, namely the display space, this means that the display room must be arranged and built first from other rooms and must be arranged regarding its strategic location. Using the ARC and TCR analysis methods, solutions or improvements and efficiency can be known for the layout at Sahabat Mart, namely the parking room is close to the warehouse room, then the warehouse room is close to the display room, the display room is close to the seating room and cashier, finally the seating room and cashier are close to the toilet room.